Intention to practice agriculture among urban dwellers in the Klang Valley Malaysia - Ngahdiman, Ida Naziera (2017)
Urban agriculture gained popularity among the urban dwellers since the issues of food security and the migration of people from the rural to the urban areas cropped up and caused the food demand to increase drastically. As a result of urbanization, most of the lands available for farming are now being converted into housing units, industries as well as for the construction of highways. In addition, there is an increase in the trend of rural migration to urban areas for employment opportunities and social amenities.